O-093 Male translocations in recurrent pregnancy loss: Natural conception versus PGD treatment: what is the right option?: A systematic review and meta-analysis. (6th August 2021) - Cardenas Armas, D; Duran-Retamal, M; Odia, R; Cawood, S; Drew, E; Yasmin, E; Saab, W; Serhal, P; Seshadri, S
Abstract: Study question: Does PGD treatment in couples with a history of RPL due to male translocations improve the outcome, increasing LBR and reducing miscarriage rate and time taken to live birth? Summary answer: Live birth rate is significantly increased, miscarriage rate is significantly reduced using PGD. Time taken to achieve live birth rate is shorter in PGD treatment. What is known already: Reciprocal translocation are the most common structural rearrangement in infertile men. The specific chromosomes and breakpoints involved might play an important role, often expressed as abnormal semen parameters or repeated pregnancy loss (RPL). The genetic counselling of these men remains challenging. Previous studies and meta-analysis performed showed no difference in live birth rate when comparing natural conception versus PGD treatment. However, the difference in miscarriage rate and time to live birth between PGD and natural conception has not been reported before in the medical literature. Study design, size, duration: A systematic review of the literature was conducted through MEDLINE, EMBASE, and the Cochrane database up until December 2020. A comprehensive search yield 287 articles, 25 of which were included for abstract reading, finally, six were included in the meta-analysis. Participants/materials, setting, methods: The six selected articles, reported on Live birth rate (LBR), miscarriage rate and time to live birth (TTLB) for natural conception compared to PGD for the same cohort of patients. All of the included articles were of retrospective design. The primary outcome was the comparison in LBR and the second outcome was the analysis in miscarriage rate and TTLB in the PGD group versus natural conception. Main results and the role of chance: A total of 1438 couples that conceived naturally, had a LBR of 22.46%, compared with 43, 17% among 681 couples that underwent PGD (0.53 95% CI (0.43-0.65) p o < 0, 00001). The six articles included in this meta-analysis had significant homogeneity (I 2 = 96%). Comparison of miscarriage rates, natural conception represented 1339 miscarriages out of 1836 pregnancies, in comparison with 44 miscarriages out of 558 pregnancies achieved through PGD. The OR showed a 10 fold increase risk of miscarriage when conceiving naturally in couples with a male translocation (10.18; 95% CI (2.88-36.04) p = 0.0003). Regarding TTLB, the difference was not statistically significant, however it did reflect that PGD patients will have a shorter TTLB (3.56 95% CI (-0.88-8.00)p = 0.12). One of the studies included, took into account the waiting list to access PGD funding, prolonging therefore the TTLB in the PGD group. Limitations, reasons for caution: The main limitation of this study is the low number of studies. TTLB should be interpreted with caution given that one of the articles included the time of the waiting lists. More studies could demonstrate a shorter time period for these couples to conceive and have a successful ongoing pregnancy. Wider implications of the findings: First study to demonstrate the value of PGD in decreasing miscarriage rates in couples with RPL. Specially when counselling couples with history of RPL with male translocations. PGD should be offered in these couples to improve the outcome, and to diminish the physical, emotional and sequelae of RPL and TOP. Trial registration number: not applicable